Composition and influencing factors of professionals’ capacity in public health emergency rescues: a qualitative study - Zhong, Fangfang; Lin, Yin; Chen, Ying; Gao, Yazhuo; Zhu, Xuehua (Frontiers in Public Health, 2024)
Objectives: To explore the composition and influencing factors of professionals' capacity in public health emergency rescues. Methods: The study adopted a descriptive qualitative method. The researchers recruited medical workers, managers and members of the emergency rescue team in Hangzhou, Zhejiang, to participate through a purposive sampling method. This study collected the data using semi-structured interviews and analyzed it through a conventional content analysis method. Results: 2 themes and 13 sub-themes emerged from the analysis: ability composition (knowledge reserve, early warning assessment, information reporting, emergency response, public health response, personal ability, coordination and cooperation, health education) and influencing factors (educational background, region, experience, hospital level, human resources and financial investment).The study on the composition and influencing factors of professionals' capacity in public health emergency rescues can provide the basis for the construction of relevant indicator system, and provide a reference for relevant departments to further optimize the emergency education and training mode, strengthen emergency drills, and improve the actual combat ability. At the same time, it is necessary to pay attention to the construction of emergency rescue team, adjust the ratio of personnel, improve the remuneration, and mobilize the work enthusiasm, to improve the emergency rescue ability.